The effect of pressure on the radiative efficiency of InAs based light emitting diodes - Choulis, Stelios A.; Andreev, Aleksey D.; Merrick, Michael L. (My University, 2003)
The spontaneous emission of 3.3 μm light emitting diodes (LEDs) and lasers based on InAs alloys were studied as a function of hydrostatic pressure. An increase in light output with increasing pressure has been observed, with a general comparison of the performances of type I and type II structures given in terms of the radiative and non-radiative processes involved. The experimental results provide evidence that the so-called CHSH Auger process is insignificant in these devices. However, Auger recombination mechanisms are still shown to dominate the response of these type II LEDs in contrast to type I lasers where competing radiative processes appear more significant
Keywords: Light emitting diodes; Hydrostatic pressure